Professional Identity in Guidance and Counseling: The Perspective of Prospective Counselors - Rahman, Fathur; Nurmalasari, Yuli; Aminah, Siti; Taufiq, Agus (Jurnal Kajian Bimbingan dan Konseling, 2022)
This study aims to describe prospective counselors’ perceptions of professional identity concepts in the guidance and counseling field. This study used a qualitative approach with an exploratory, descriptive design. Research data were collected through open questionnaires and focus group discussions. The data sources were fifteen guidance and counseling students from three different classes. Data analysis was carried out by searching for themes and determining the correlation between them to attain interpretation. The results of the study show that professional identity is conceptualized as a typical characteristic or a symbol of professional conduct in the profession of guidance and counseling. Meanwhile, the dimensions of professional identity according to students are categorized into professional competence, personality, personal appearance, knowledge of the profession, and professional ethos. Lastly, for the student, professional identity is something that moves dynamically.